Analisis Sebaran Tenaga Kesehatan Puskesmas di Indonesia berdasarkan Peraturan Menteri Kesehatan Nomor 75 Tahun 2014 tentang Puskesmas - Yuni Sari Romadhona; Kemal N. Siregar (Politeknik Kesehatan Kemenkes Mamuju, 2018)
The persistent problem faced by Indonesia is in adequate in number and maldistribution of health workers in Primary Health Centre (PHC) has resulted in disrupted health services to the community. The aims of this study is describe health workers in ratio PHC per 100,000 population and health workers distributionbyregions. This research is descriptive analytic. The data used are secondary data from the health workers in government health care facilities in the district/city and province in Indonesia collected by Sub Centre data and information of health ministry in June 2018 and analyzed using the chi-square. The fact that inadequate numbers and maldistributionare remaining problems of health workers in PHC. The ratio of physiciansis 10,17, midwifes 84,73, nurses 83, Public health services 11,09 and nutritionists 8,30 per 100,000 populations while Government standards are higher. Maldistributions of health workers in PHC occurred in central and east regions of Indonesia. The highest number of health workers at PHC in Indonesian is midwives and nurses, while the smallest workforce is dentists. As in adequate numbers and maldistribution are the remaining problems of health workers in PHC, the recruitment of health workers should fulfil the community needs, geographic and avalaibility of health services. Providing the government scholarship to the locals in health schools with commitment to work for local government after graduation is one of the solution for this problem. E-health service is another solution, health service consultation can be carried out effectively and efficiently with remote health experts by taking the advantage of the internet.